Instant notes : biochemistry - Hames, B. D. (Instant notes series., 2000)
Instant Notes in Biochemistry, 2/e provides an easy access to the fundamentals in this field. The book is a major update on the very successful first edition with expanded coverage of transcription, RNA processing and protein synthesis and many additional new topics. New illustrations have been added and much of the artwork has been enlarged or redrawn to aid comprehension.